Marxian economics - Desai, Meghnad (Oxford, 1979)
This book contributes to the debate on Marxian economics which has, in the 1970s, begun to receive renewed attention in the West. Much new material on the subject is being translated into English even now. Drawing on these latest sources together with what has otherwise been available, and using modern quantitative techniques, Desai argues that Marx's value theory differed from both Ricardo's and that of the Neoclassicists. In Marx, value theory. plays the crucial role of drawing out, or illuminating, the influence of the class struggle in capitalism on relations of economic exchange. Clearly, Marx's labour theory of value was not a theory. of relative prices or resource allocation alone; it was a much broader concept which embraced social relationships as well.
Keywords: Marxian economics